High performance activated carbon anodes for supercapacitors for energy storage applications - THOMAS FONE (2023)
This work presents the optimisation of an activated carbon ink using Ethyl Cellulose as a binder for application as electrodes in supercapacitors. Effect of variation in the concentration of Ethyl Cellulose binder was explored adopting a commercially available Activated carbon as reference. The result was that the 10% EC concentration led to the best performance compared to the 20% and 5% EC inks, with a specific capacitance of 62.3F/g at 1.4A/g. It was hypothesised that the 20% EC ink had too much binder, potentially clogging up the pores in the activated carbon, while the 5% EC ink did not have enough binder, causing decohesion of the ink from the substrate, which severely limited the performance of the electrode. As part of the work, a special carbon provided by the sponsoring company was also tested using the same 10% EC recipe only substituting the new carbon instead of the commercial one. Particle size analysis of this carbon showed that the particles had a larger disparity of sizes compared to the commercial activated carbon. This new carbon gave a better result of 82.7F/g at 1.4A/g even with the particle size disparity.